Application for Employee Performance Assessment Using Profile Matching Method - Aisyah, Siti; Purba, Windania; Harahap, Mawaddah; Husein, Amir Mahmud (Politeknik Ganesha Medan, 2019)
Human resources an important role for the agency. Good employee performance can provide a good image for the company. Many companies give rewards or rewards to their employees for their work performance. The assessment is done in addition to giving or appreciation as well as motivation for employees to work better. Problems that often occur in the employee appraisal process are the large number of employees and the criteria assessed and data processing are still in conventional process so that takes a long time and the results of the assessment are still not objective. To overcome, application was built could simplify the employee performance appraisal process. The method used is Profile Matching to assess and determine employees who excel. Factors or criteria used in the form of performance, discipline, honesty, years of service, cooperation. Profile matching is broadly the process of comparing the actual data value of a profile to be assessed with the expected profile value. Application is built based on web with PHP programming and MYSQL. To help the process of employee performance appraisal at Universitas Prima Indonesia. Collecting data in research using literature studies, observations, interviews, and sampling. Result the research is Profile Matching Method can be use for Decision Support System in determining employee achievement, with the highest calculation results in the sample data obtained by A3 and the lowest position obtained by A1. In academic, research can be an enrichment of teaching materials especially in subject of Decision Support Systems and information systems in general.